Computational analysis of antiviral drugs against South African (B.1.351) SARS-CoV-2 spike protein variant - Ferrari, I.V.; Mario, M. Di (International Journal of Scientific Research in Computer Science and Engineering, 2021)
The present work is intended to study, through the “Molecular Docking” approach, about 100 antiviral drugs, against the South African (B.1.351) SARS-CoV-2 spike protein variant. The analysis was performed by Autodock Vina, in which we scan the active area of three key amino acids belonging to the Spike Protein RBD, responsible for a higher binding with the ACE2 receptor. They are ASN 417; Lys 484, and Tyr 501 respectively. From our results, we have found out five potential inhibitor drugs of the hepatitis C virus (HCV ), which have been shown a good Binding Energy score of -10 kcal mol-1. They are Furaprevir, Simeprevir, Odalasvir, and Paritaprevir respectively. In addition, their best-docked pose can bind to two of the three investigated residues of the Spike-RBD, which are N 417 and Y 501. As known, these last residues have been found in other Coronavirus variants as the most recent case of the Omicron one.